Neonatal intracranial hemorrhage due to rupture of arteriovenous malformation - BİLGEN, HÜLYA SELVA (ELSEVIER SCIENCE INC, 1996)
Two cases of neonatal intracerebral hemorrhage secondary to rupture of arteriovenous malformation are reported and the pertinent literature is reviewed, Despite the limited number of cases, review of the literature and our results demonstrate that the outcome of surgical removal of an arteriovenous malformation in the neonatal period is not as poor as was previously believed.